VALUE DEVIATIONS IN SOCIAL NETWORKS AS A THREAT TO THE SOCIO CULTURAL DEVELOPMENT OF UKRAINE - Євген Миколайович Мануйлов; Юрій Юрійович Калиновський (Вісник НЮУ імені Ярослава Мудрого: Серія: Філософія, філософія права, політологія, соціологія, 2021)
Problem setting. Nowadays, social networks have become an integral part of communication processes in society. The influence of social networks on the socio-cultural development of Ukraine has both positive and negative manifestations, since both values and antivalues are spread in these communication systems, there are subjects who are guided by the norms of morality and law, and those who neglect them, direct their efforts to the harmonization of a certain sphere of public life, or vice versa, produces xenophobic sentiments, inciting enmity in the domestic society at the cultural, national, religious and other levels. Recent research and publications analysis. Significant numbers of scientific works are aimed at elucidating the signs and criteria of deviating as a social phenomenon. According to A. Demkiv, those values, the worldview and behavior that deviate from the organizational culture that exist in a certain social community are considered deviant. In the context of this research, it is important to note A. Khlebnikova's reflections on the recognition and determination of the axiological status of the social network in modern society and the scientific work of P. Kravchenko, which proves that religion, morality, values, language, traditions contribute to the internal consolidation of local social groups, and in this process, social networks perform a leading role. Researchers A. Onishchenko, V. Gorovoy, V. Popik and others devoted their scientific research to uncovering the negative impact of social networks on the development of the Ukrainian state and its socio-cultural and informational spheres. Paper objective. This research involves the disclosure of the negative impact of value deviations of social network subjects on the domestic socio-cultural area, information and spiritual security of Ukraine. Paper main body. The wide range of values presented in social networks has a consolidating, humanistic nature – they are reproduced by scientific and creative communities, spiritual and cultural associations, volunteer and human rights organizations, and so on. In turn, anti-values are presented in the content of extremist organizations, xenophobic associations of various orientations, which creates an ideological basis for the emergence of social conflicts, disintegration processes, and civil confrontation. Thus, social networks have become an influential actor in the development of the socio-cultural, spiritual, value, information space of our country. Considering Ukrainian society as a holistic formation, it is worth noting that value deviations are those ideas about the ways of being and about spiritual life that do not correspond to the humanistic and national guidelines for the democratic development of Ukrainian society. In the context of the research, worldview guidelines that contradict moral attitudes, existing legal norms, accepted traditions of the domestic society, etc. can be considered as value deviations in social networks. Freedom in social networks has a dual manifestation: on the one hand, it is free opportunities for self-realization of individuals and diverse perspectives for the development of the country's socio‑cultural space, and on the other hand, freedom in social networks creates conditions for the popularization of antihuman attitudes, pseudo-values, xenophobic ideologies and worldview systems. Conclusions of the research.  The value deviations of social network subjects are a logical continuation of the deformations of the moral, political, legal, spiritual and other humanistic direction attitudes that are widespread in Ukrainian society. Undoubtedly, the influence of value deviations on domestic socio-cultural development is destructive and it can manifest itself in illegal, immoral, aggressive models of behavior.